Transient Isotopic Kinetic Study of the NO/H2/O2 (Lean de-NOx) Reaction on Pt/SiO2 and Pt/La-Ce-Mn-O Catalysts - Costa, Costas; Efstathiou, A. M. (My University, 2004)
Steady-state isotopic transient kinetic analysis (SSITKA) coupled with temperature-programmed surface reaction (TPSR) methods and using in situ mass spectroscopy and DRIFTS have been applied for the first time to study essential mechanistic aspects of the NO/H2/O2 reaction at 140 °C under strongly oxidizing conditions over 0.1 wt % Pt/SiO2 and 0.1 wt % Pt/La−Ce−Mn−O catalysts. The nitrogen-pathway of the reaction from NO to form N2 and N2O gas products was probed by following the 14NO/H2/O2 → 15NO/H2/O2 isotopic switch at 1 bar total pressure. It was found that the chemical structure of active intermediate NOx species strongly depends on support chemical composition. In the case of the Pt/SiO2 catalyst, the reaction route for N2 and N2O formation passes through the interaction of one reversibly and one irreversibly NOx species chemisorbed on the Pt surface. On the other hand, in the case of a Pt/La−Ce−Mn−O catalyst, the reaction route passes through the interaction of two different in structure irreversibly chemisorbed NOx species on the support. For the latter catalyst, the mechanism of the reaction must involve a hydrogen-spillover process from the Pt metal to the support surface. A surface coverage θ = 1.8 (based on Pt metal surface) of active NOx intermediate species was found for the Pt/La−Ce−Mn−O catalyst. A large fraction of it (81.5%) participates in the reaction path for N2 formation, whereas in the case of Pt/SiO2, this fraction was found to be 68.4% (active NOx, θ = 0.65). These important results provide an explanation for the lower N2 reaction selectivity values observed on Pt/SiO2 compared to Pt/La−Ce−Mn−O catalyst. Inactive adsorbed NOx species (spectators) were found to accumulate on both Pt and support surfaces. It was found via the NO/H2/16O2 → NO/H2/18O2 isotopic switch that the reaction path from NO to form N2O passes through the oxidation step of NO to NO2 with the participation of gaseous O2, where the extent of it depends on support chemical composition.
Keywords: Silica-supported platinum; Noble-metal catalysts; Model 3-way catalysts; Nitric-oxide; Steady-state; Low-temperatures; Heterogeneous catalysis; NO/C3H6/O-2 reaction; Surface-composition; Mechanistic aspects